Determinants of Outcome in Hospitalized Patients With Methicillin-Resistant Staphylococcus aureus Bloodstream Infection: Results From National Surveillance in Canada, 2008-2012. (19th January 2016) - Simor, Andrew E.; Pelude, Linda; Golding, George; Fernandes, Rachel; Bryce, Elizabeth; Frenette, Charles; Gravel, Denise; Katz, Kevin; McGeer, Allison; Mulvey, Michael R.; Smith, Stephanie; Weiss, Karl
Abstract : BACKGROUND: Bloodstream infection (BSI) due to methicillin-resistant Staphylococcus aureus (MRSA) is associated with considerable morbidity and mortality. OBJECTIVE: To determine the incidence of MRSA BSI in Canadian hospitals and to identify variables associated with increased mortality. METHODS: Prospective surveillance for MRSA BSI conducted in 53 Canadian hospitals from January 1, 2008, through December 31, 2012. Thirty-day all-cause mortality was determined, and logistic regression analysis was used to identify variables associated with mortality. RESULTS: A total of 1, 753 patients with MRSA BSI were identified (incidence, 0.45 per 1, 000 admissions). The most common sites presumed to be the source of infection were skin/soft tissue (26.6%) and an intravascular catheter (22.0%). The most common spa types causing MRSA BSI were t002 (USA100/800; 55%) and t008 (USA300; 29%). Thirty-day all-cause mortality was 23.8%. Mortality was associated with increasing age (odds ratio, 1.03 per year [95% CI, 1.02–1.04]), the presence of pleuropulmonary infection (2.3 [1.4–3.7]), transfer to an intensive care unit (3.2 [2.1–5.0]), and failure to receive appropriate antimicrobial therapy within 24 hours of MRSA identification (3.2 [2.1–5.0]); a skin/soft-tissue source of BSI was associated with decreased mortality (0.5 [0.3–0.9]). MRSA genotype and reduced susceptibility to vancomycin were not associated with risk of death. CONCLUSIONS: This study provides additional insight into the relative impact of various host and microbial factors associated with mortality in patients with MRSA BSI. The results emphasize the importance of ensuring timely receipt of appropriate antimicrobial agents to reduce the risk of an adverse outcome. Infect. Control Hosp. Epidemiol. 2016;37(4):390–397